Probity auditing: keeping the bureaucrats honest? - Shead, Bob (2001)
The use of probity audits has flourished in the public sector in recent years. This growth has been accompanied by the development of probity guidelines by a number of central agencies and infrastructure providers across Australia. However, these guidelines tend to focus on competitive procurement processes and ignore broader factors applying to other processes in which probity audits are also used. Further, as there are no professional standards governing a probity audit (unlike most other types of audit), it is important that agencies have a clear understanding of their benefits and limitations and of the skills and experience required of a probity auditor before they commission one. - Reproduced
Keywords: Civil service; Audit